2005
DOI: 10.1097/01.prs.0000152422.64505.2a
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Site Morbidity of the Pedicled Rectus Femoris Muscle Flap

Abstract: The rectus femoris muscle flap is well known for its reliable anatomy, the ease with which it can be harvested, and its great versatility. As a pedicled or free flap, it is used to cover soft-tissue defects and to recreate motor function. Although the muscle is very reliable, it is not well respected because of its assumed donor-site morbidity, such as weakened knee extension force and decreased range of motion of the knee. To date, these clinical assumptions have only rarely been quantified in terms of object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…We attribute this in part to our efforts to centralize the remaining quadriceps femoris by approximating the distal third of the medial and lateral vastus muscles during closure, which has been suggested to assist in the maintenance of donor site biomechanics [13,15]. Furthermore, we advocate for the incorporation of a structured, graduated rehabilitation program, postoperatively, which has been shown to improve donor site strength and stability following harvest of the rectus femoris and is likely a significant contributor to the excellent functional outcomes and lack of appreciable donor site deficits observed in this case [14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…We attribute this in part to our efforts to centralize the remaining quadriceps femoris by approximating the distal third of the medial and lateral vastus muscles during closure, which has been suggested to assist in the maintenance of donor site biomechanics [13,15]. Furthermore, we advocate for the incorporation of a structured, graduated rehabilitation program, postoperatively, which has been shown to improve donor site strength and stability following harvest of the rectus femoris and is likely a significant contributor to the excellent functional outcomes and lack of appreciable donor site deficits observed in this case [14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…These flaps have been demonstrated to improve the rate of vascular graft salvage with minimal donor site morbidity. [8][9][10] Early debridement and muscle flaps reduce graft sepsis and increase limb salvage in complicated groins and can also be efficacious in treating lymphatic complications. [11][12][13] Overall, it has been shown that early use of muscle flaps improves wound healing and graft salvage while reducing costs.…”
mentioning
confidence: 99%
“…There have been several studies that evaluated functional morbidity after rectus femoris harvest and this has been found to be well tolerated and, if proper physical therapy performed, compensated completely by remaining musculature. 20,21 Although we are unaware of any studies performing formal strength testing after gracilis or vastus lateralis flap harvest, functional loss at these donor sites is reported to be minimal. 5,6,22 Finally, surgeons in this study chose flaps as per their clinical judgment.…”
Section: Discussionmentioning
confidence: 99%